Effect of Compost Properties on Progress Rate of Verticillium dahliae Attack on Eggplant (Solanum melongena L.). Issue 2 (3rd April 2018) - Kanaan, Housam; Hadar, Yitzhak; Medina, Shlomit; Krasnovsky, Arkady; Mordechai-Lebiush, Sara; Tsror (Lahkim), Leah; Katan, Jaacov; Raviv, Michael
ABSTRACT: Several composts were tested for their capacity to moderate the effect of Verticillium dahliae Kleb. (VCG B4, VD) on eggplant ( Solanum melongena ) under greenhouse conditions. Eggplants plantlets were inoculated by immersing their roots in conidial suspension and then planted in pots filled with mixtures of compost or peat moss, mixed with perlite. Six composts and peat moss mixtures were tested, of which tomato waste compost suppressed V. dahliae, and turkey litter compost partially suppressed it. Reduced levels of symptoms and lower fungal colonization were detected in the xylem of eggplants planted in tomato waste compost, and these plants accumulated more dry matter and had higher chlorophyll content compared to other media. However, survival of conidia in tomato waste compost showed only a moderate decrease compared with a sharp decrease in other media, suggesting that conidial eradication cannot be proposed as the suppressiveness mechanism. γ irradiation of tomato waste compost and peat at 2.5 Mrad reduced microorganism density by four orders of magnitude, but irradiation of tomato waste compost did not reduce its suppressiveness of V. dahlia e. Composts properties affected progress rate of VD in the xylem tissue of eggplant seedling. These properties could indicate both biotic and abiotic factors affecting the process.